The prediction of the nutritive value of forages by means of an in vitro enzyme digestion technique - Niemann, P. J.(Pieter Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric) -- University of Stellenbosch, 1968.